Impact of Resilience on the Performance Optimisation of SMEs: Evidence from the Manzini Region, Eswatini - Kule, Julius Warren; Kanyangale, MacDonald (The Journal of Accounting and Management, 2025)
Resilience is essential for small and medium enterprises (SMEs) in Eswatini to adapt and thrive amid disruptions. This study investigated the relationship between resilience and performance optimisation in SMEs. While previous research recognises the importance of resilience in overcoming organisational performance challenges, the specific mechanisms through which resilience influences performance remain underexplored. Using census sampling, data were collected from 206 owner-managers of SMEs in Manzini through a self-administered questionnaire. Cronbach’s alpha was used to test for reliability. At the same time, Pearson’s correlation coefficients were employed to examine the bivariate associations between the resilience dimensions and performance optimisation. The findings reveal significant positive correlations between the resilience dimensions: detectability (r = 0.372, p < 0.01), coping (r = 0.200, p < 0.01), and adaptation (r = 0.245, p < 0.01) and performance optimisation. These results recognise resilience as a multi-dimensional and dynamic process requiring strategic actions before, during, and after adverse events. This study contributes valuable insights for SME owners and policymakers by demonstrating how integrating detectability, coping, and adaptation strategies can build resilience and optimise performance in disruptive environments.